False Belief vs. False Photographs: A Test of Theory of Mind or Working Memory? - Callejas, Alicia; Shulman, Gordon L.; Corbetta, Maurizio (Frontiers in Psychology, 2011)
Theory of Mind, the ability to reason about other people’s thoughts and beliefs, has been traditionally studied in behavioral and neuroimaging experiments by comparing performance in ‘false belief’ and ‘false photograph’ (control) stories. However, some evidence suggests that these stories are not matched in difficulty, complicating the interpretation of results. Here, we more fully evaluated the relative difficulty of comprehending these stories and drawing inferences from them. Subjects read false belief and false photograph stories followed by comprehension questions that probed true (‘reality’ questions) or false beliefs (‘representation’ questions) appropriate to the stories. Stories and comprehension questions were read and answered, respectively, more slowly in the false photograph than false belief conditions, indicating their greater difficulty. Interestingly, accuracy on representation questions for false photograph stories was significantly lower than for all other conditions and correlated positively with participants’ working memory span scores. These results suggest that drawing representational inferences from false photo stories is particularly difficult and places heavy demands on working memory. Extensive naturalistic practice with ToM reasoning may enable a more flexible and efficient mental representation of false belief stories, resulting in lower memory load requirements. An important implication of these results is that the differential modulation of right temporal-parietal junction (RTPJ) during ToM and ‘false photo’ control conditions may reflect the documented negative correlation of RTPJ activity with working memory load rather than a specialized involvement in ToM processes.